Current Account and Real Exchange Rate Dynamics in the G-7 Countries - Chinn, Menzie (IMF Working Papers; Working Paper ;, 2002)
The canonical predictions of intertemporal open-economy macro models are tested by a structural VAR analysis of Group of Seven countries. The analysis is distinguished from the previous literature in that it adopts minimal assumptions for identification. Consistent with a large set of theoretical models, permanent shocks have large long-term effects on the real exchange rate but relatively small effects on the current account; temporary shocks have large effects on the current account and exchange rate in the short run, but not on either variable in the long run. The signs of some impulse responses point toward models that differentiate tradables and nontradables.